2016
DOI: 10.1099/jgv.0.000632
|View full text |Cite
|
Sign up to set email alerts
|

Pre-infection transcript levels of FAM26F in peripheral blood mononuclear cells inform about overall plasma viral load in acute and post-acute phase after simian immunodeficiency virus infection

Abstract: CD8+ cells from simian immunodeficiency virus (SIV)-infected long-term non-progressors and some uninfected macaques can suppress viral replication in vitro without killing the infected cells. The aim of this study was to identify factors responsible for non-cytolytic viral suppression by transcriptional profiling and to investigate their potential impact on SIV replication. Results of microarray experiments and further validation with cells from infected and uninfected macaques revealed that FAM26F RNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Comparison of viral acquisition between the controls and 10 unvaccinated animals from another experiment infected with the same virus stock and dose by the same route showed that our challenge protocol yielded reproducible results (36). Inclusion of these historical controls in the calculations resulted in a reduction of the observed infection risk per exposure, relative to controls, of 75% for V2 (HR ϭ 0.248; 95% CI, 0.087 to 0.712; P ϭ 0.012).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Comparison of viral acquisition between the controls and 10 unvaccinated animals from another experiment infected with the same virus stock and dose by the same route showed that our challenge protocol yielded reproducible results (36). Inclusion of these historical controls in the calculations resulted in a reduction of the observed infection risk per exposure, relative to controls, of 75% for V2 (HR ϭ 0.248; 95% CI, 0.087 to 0.712; P ϭ 0.012).…”
mentioning
confidence: 76%
“…IFN-␥ levels were significantly higher in V2 than in V1 (Mann-Whitney test; P ϭ 0.008) ( Fig. 7E) and correlated with the relative RNA levels of FAM26F and CXCL10 (FAM26F, r s ϭ 0.67, P Ͻ 0.0001 [36]; CXCL10, r s ϭ 0.69, P ϭ 0.015 [data not shown]). Surprisingly, in contrast to IFN-␥, plasma CXCL10 levels were significantly higher in V1 than in V2 (Mann-Whitney test; P ϭ 0.026 at 24 h and P ϭ 0.017 at 48 h) (Fig.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…Various whole transcriptome analyses have demonstrated FAM26F to be differentially expressed in several viral (Simian Immunodeficiency Virus and Hepatitis C Virus (HCV)) [ 10 , 11 ], bacterial (Septicemic melioidosis, Staphylococcal Superantigens, and Staphylococcal Enterotoxin B) , [ 12 14 ], and parasitic infections like Gastrointestinal Nematode infection [ 15 ], in liver transplantation, and in several cancers (breast, mammary gland, cervix, and uterus) [ 16 ]. With respect to viral infections, FAM26F has only been studied in SIV [ 17 ] and HCV [ 11 ]. In SIV-infected Rhesus macaques, pre-infection levels of FAM26F were found to correlate with the overall viral load during the acute phase of infection, recognizing FAM26F as one of the earliest prognostic markers which can give information related to the pace and strength of antiviral immune response [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 3 Moreover, investigating its function in SIV infection showed that pre-infection levels of FAM26F correlate inversely with general viral load of plasma, and thus, FAM26F can be regarded as one of the earliest prognostic markers which, in the infection’s early stage, can give us information related to the pace and strength of antiviral’s immune response. 4 …”
Section: Introductionmentioning
confidence: 99%